A Pilot Study: Comparison of Arm Versus Ankle Noninvasive Blood Pressure Measurement at 2 Different Levels of Backrest Elevation. Issue 4 (July 2015) - Henley, Nicole; Quatrara, Beth D.; Conaway, Mark
Abstract : Background: Standard practice for obtaining noninvasive blood pressure includes arm blood pressure (BP) cuff placement at the level of the heart; however, some critical care patients cannot have BPs taken in their arm because of various conditions, and ankle BPs are frequently used as substitutes. Objective: The aim of this study was to determine if there was a significant variation between upper arm and ankle BP measurements at different backrest elevations with consideration of peripheral edema factors. Methodology: After institutional review board approval was obtained, a pilot study was implemented to evaluate noninvasive BP measurements of the arm and ankle with backrest elevation at 0° and 30° in a population of medical intensive care unit patients. Participants served as their own controls and were randomly assigned to left- versus right-side BP readings. Data were also collected on presence of arm versus ankle edema. Results: A total of 30 participants enrolled in the study and provided 120 BP measurements. Blood pressure readings were analyzed in terms of diastolic and systolic findings as well as backrest elevations and edema presence. Thirteen participants presented with either arm or ankle edema. There was a statistical difference between the systolic arm and ankle BP measurements in the 0° (P = .008) and 30° (P < .001) backrest elevation positions. The correlation between arm and ankle diastolic BP is greater for participants without ankle edema (P = .038, r = 0.54) than for participants with ankle edema (P = .650, r = 0.14), but it is not statistically significant (P = .47). Discussion: Even though ankle BPs are often substituted for arm BPs when the arm is unable to be used, ankle BPs and arm BPs are not interchangeable. Adjustments in backrest elevation and considerations of edema do not normalize the differences. Blood pressures obtained from the ankle are significantly greater than those obtained from the arm. This information needs to be considered when arms are not available and legs are used as surrogates for the upper arm.